RANCANG BANGUN SISTEM PEMANTAUAN KONDISI AIR KOLAM IKAN BERBASIS IOT - Aura Putra, Dimas; Zulkarnain, Habib; Febriansyah, Aan; Mubaroh, Sari (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Monitoring of water levels in fish ponds is rarely done. Uncontrolled water discharge due to heavy rainfall can cause a pond to overflow and evaporate water due to the dry season due to lack of information on the pond. This is because the water control system in the pond is still manual. This manual method has a disadvantage factor that does not automatically add and reduce water. The application of IoT technology is a prototype for monitoring water levels and water temperatures in fish ponds with an ESP32 microcontroller. The temperature sensor we use is the DS18B20 temperature sensor to measure the temperature of the fish pond water. While the ultrasonic sensor to measure the water level of the pond which functions as an input signal for both water pumps where if the water level is below 27 cm the fish pond water filling pump is active and the water level is above 27 cm the fish pond water discharge pump is active. The results of the trial, the accuracy of the ultrasonic sensor when compared to measurements using a meter is 95.84 percent. While the DS18B20 temperature sensor when compared to measurements using a thermometer is 98.26 percent. Testing the monitoring system using Blynk software can display the display data results on the LCD, but it cannot be used to control the condition of the fish pond.